ANALYSIS OF POLICE SUPER APP INNOVATION IMPLEMENTED IN THE RANKS OF THE NATIONAL POLICE IN PUBLIC SERVICES IN THE COMMUNITY: Analisis Inovasi Polri Super App di Implementasikan di Jajaran Polri dalam Pelayanan Publik di Masyarakat - Saputra, Galuh Febri; Yopan, Muhamad (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
In the era of digitalization, crime has also evolved both in terms of methods and types. The Indonesian National Police (POLRI) as a law enforcement institution is faced with increasingly complex challenges in carrying out its duties to maintain public security and order. To overcome this challenge, the National Police has taken a number of initiatives, including the application of the latest information technology, one of which is through the development of the National Police Super App. This research is a mixed methids research with data collection methods in the form of interviews and questionnaires. The results of the study show that in the last two years, the trend of crime in Indonesia has shown an increasing trend, as reflected in the data on the number of cases handled by law enforcement officials. In 2023, the percentage of crime cases recorded at 74.25%, and this figure will increase to 75.34% in 2024. In response to this, the National Police has pursued various strategic steps, one of which is through the digital transformation of public services, including the launch and development of the National Police Super App. This application allows the public to report criminal incidents more quickly, easily, and efficiently. With a digital system, reporting becomes more documented and can be immediately followed up by the relevant police units. To increase the effectiveness of the National Police Super App, an optimization strategy is needed that covers various aspects, ranging from improving infrastructure to socialization to the community. The success of a public service application is not only determined by the technology used, but also by the extent to which the public understands and wants to use it. Therefore, the police need to take a more comprehensive approach in the development of this application. One of the main strategies that can be done is to improve the technology infrastructure, including optimizing servers to be able to handle the surge in users, as well as the development of more responsive and easy-to-use features.